2001
DOI: 10.1046/j.1523-1747.2001.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Papillon–Lefèvre Syndrome: Mutations and Polymorphisms in the Cathepsin C Gene

Abstract: The Papillon-Lefèvre syndrome, inherited in an autosomal recessive pattern, manifests with palmoplantar keratoderma and early, destructive periodontitis. Recently, mutations in the gene encoding cathepsin C have been disclosed in a limited number of families with Papillon-Lefèvre syndrome. We have examined two multiplex families with Papillon-Lefèvre syndrome, and evaluated the gene encoding cathepsin C for mutations. The mutation detection strategy consisted of polymerase chain reaction amplification of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…In addition to disease-causing missense mutations, three missense alterations have been identified in the CTSC gene that are not associated with any disease phenotype (Allende et al, 2001;Nakano et al, 2001;Lefèvre et al, 2001). Sequence analyses of the CTSC exon 3 identified no additional polymorphism other than the previously reported c.458C>T, which results in a T153I substitution in the CTSC protein.…”
Section: G139 R272 L381mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to disease-causing missense mutations, three missense alterations have been identified in the CTSC gene that are not associated with any disease phenotype (Allende et al, 2001;Nakano et al, 2001;Lefèvre et al, 2001). Sequence analyses of the CTSC exon 3 identified no additional polymorphism other than the previously reported c.458C>T, which results in a T153I substitution in the CTSC protein.…”
Section: G139 R272 L381mentioning
confidence: 99%
“…To date more than 30 different mutations of the cathepsin C gene (CTSC, MIM# 602365), have been identified in patients with PLS and related conditions (Hart et al, 1999;Toomes et al, 1999;Zhang et al, 2001;Gorlin, 2001;Allende et al, 2001;Nakano et al, 2001;Lefèvre et al, 2001; http://www.genetics.pitt.edu/CTSC). All CTSC missense mutations described to date alter evolutionarily conserved amino acid residues (Hart et al, 2000;Nakano et al, 2001). Here we report four mutations in the CTSC gene in three unrelated, ethnically diverse families from North America.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously elucidated the genetic organization of the gene encoding cathepsin C (CTSC, MIM# 602365) and have demonstrated mutations of this gene that result in a complete loss of CTSC activity in individuals affected with PLS [Toomes et al, 1999]. Further mutations of CTSC in PLS have been reported by others [Hart et al, 1999[Hart et al, , 2000aAllende et al, 2001;Lefèvre et al, 2001;Nakano et al, 2001;Zhang et al, 2001Zhang et al, , 2002Cury et al, 2002;Nusier et al, 2002]. Mutations of CTSC have also been reported in families with prepubertal periodontitis (PPP), which is characterized by periodontitis similar to that observed in PLS, but without the palmoplantar keratosis seen in PLS [Hart et al, 2000b].…”
Section: Introductionmentioning
confidence: 99%
“…It could be speculated that some of these families may also harbor mutation located in the 5′-UTR or even the mutation detected in our study. Namely, the majority of the studies on the genetic background of PLS did not include mutational analyses of the whole 5′-UTR [10,33,36,37,38,39]. Only a limited number of studies reported analysis of the CTSC 5′-regulatory region in families from several ethnic groups; however, no mutations were discovered in the 5′-UTR [6,9,40].…”
Section: Discussionmentioning
confidence: 99%